Pengaruh Influencer Marketing, FoMO (Fear of Missing Out), dan Online Customer Review Terhadap Keputusan Pembelian Skincare The Originote di E-Commerce Shopee Pada Gen Z Kota Mataram - Husrul Linny, Emy; HS, Rusminah; Rispawati, Dewi (Postgraduate, University of Mataram, 2025)
This study aims to determine the effect of Influencer Marketing, FoMO (Fear of Missing Out) and Online Customer Review on Purchasing Decisions for The Originote skincare in Shopee e-commerce for Gen Z in Mataram city. The data collection method uses a sample survey method with a sample of 100 respondents. The analysis method uses multiple linear regression analysis using the Stastical Package For The Social Sciences (SPSS) tool. The results of this study indicate that Influencer Marketing has a positive and significant effect on Purchasing Decisions with a t value for Influencer Marketing of 4.701> 1.984 and Online Customer Review has a positive and significant effect on Purchasing Decisions with a t value for Online Customer Review of 4.393> 1.984. Meanwhile, FoMO (Fear of Missing Out) has a negative and insignificant effect on Purchasing Decisions with t count for FoMO (Fear of Missing Out) 0.778 <1.984. The results of this study can be used as a basis for improving purchasing decisions by developing the quality of Influencer Marketing, FoMO (Fear Of Missing Out) and Online Customer Reviews.